CONTRASTIVE PRAGMATICS AS A NEW DIRECTION IN LINGUISTICS (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Pragmatics, as the science of language use, cannot ignore the variability of language resources from which choices have to be made, both when producing utterances, and when interpreting them. Contrastive pragmatics is closely associated with the use of parallel and comparable corpora for studying the similarities and differences between languages. ... As a result, many contrastive studies nowadays are doubly contrastive in that they compare pragmatic phenomena across both genres and languages. The present article deals with different ways of speaking in different communities. The findings suggest that the status and role of the situation affect the speakers’ choices and semantic formulas are of great importance.